Gender dimensions of inequality in the countries of Central Asia, South Caucasus, and Western CIS - Tamar Khitarishvili (Levy Economics Institute of Bard College, 2016)
The collapse of the Soviet Union initiated an unprecedented social and economic transformation of the successor countries and altered the gender balance in a region that counted gender equality as one of the key legacies of its socialist past. The transition experience of the region has amply demonstrated that the changes in the gender balance triggered by economic shifts are far from obvious, and that economic expansion and women's economic empowerment do not always go hand in hand. Therefore, active measures to enhance women's economic empowerment should be of central concern to the policy dialogue aimed at poverty and inequality reduction and inclusive growth. In this paper, we establish the current state of various dimensions of gender inequalities and their past dynamics in the countries of Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan), South Caucasus (Armenia, Azerbaijan, and Georgia), and Western CIS (Belarus, Moldova, and Ukraine), and propose steps aimed at reducing those inequalities in the context of inclusive growth, decent job creation, and economic empowerment.
Keywords: J16; P2; 330; Gender Economics; Inequality; Transition Countries; Human Development; Western CIS; Central Asia; South Caucasus